Analyzing How English Proficiency Affects the Career Mobility of Accountants in Non-English Speaking Countries - Sitora Uktam kizi, Xasanova; Sabrina Zohid kizi, Oyyariqova (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This study analyzes how English proficiency affects the career mobility of accountants in non-English speaking countries. It explores the role of English as a global business language in accounting, auditing, and international financial reporting. The research highlights that strong English skills improve job opportunities, access to multinational companies, and participation in global financial markets. It also discusses challenges faced by accountants with limited English proficiency, including reduced career advancement and communication barriers in international workplaces. Overall, the study emphasizes that English proficiency is a key factor influencing professional growth and global career mobility in the accounting field.